"The impact of orthognathic surgery on articulation proficiency and speech intelligibility in skeletal Class III malocclusion: 18 months follow up" - Chaman Lal; Mukul Kumar; Sanjeev Verma; Vinay Kumar; Raj Kumar Verma; Satinder Pal Singh; Vidya Rattan; Sanjay Munjal (Elsevier, 2024)
Introduction: Orthognathic surgery results in the positional change of the maxilla and mandible that may affect speech. The present study evaluated the effect of combined maxillary advancement and mandibular setback surgery on articulation proficiency and speech intelligibility in patients with non-syndromic skeletal Class III malocclusion. Methods: In this prospective study, twenty-five patients with skeletal class III malocclusion and consecutively treated with Lefort-1 maxillary advancement and mandibular setback (BSSO) orthognathic surgery were included in this study. The speech sample was recorded with a digital audio tape recorder one day before surgery and at 3, 6, 9, 12 and 18 months after surgery. Three qualified and experienced speech and language pathologists evaluated articulation errors and intelligibility of speech samples. Repeated One-way analysis of variance was used to compare articulation proficiency and speech intelligibility at different time intervals. Results: The substitution, omission, distortion and addition errors showed no significant changes at 3 months and 6 months. The total articulation errors decreased to zero at 9 months and no significant increase was observed till 18 months (P < 0.05). Speech intelligibility showed statistically non-significant improvement at any time interval. Cephalometric skeletal parameters SNA and N ḻ A°. were significantly correlated with addition and total articulation errors at 18 months follow up. Conclusions: The ortho-surgical treatment improves speech (decreases. articulation errors) in most of the patients usually 6-9 months post-surgery. Speech intelligibility is not affected by bimaxillary orthognathic surgery in skeletal class III patients. The articulation errors were correlated to changes in position of maxilla.